PRINCIPLE MANAGERIAL COMPETENCE FOR IMPROVING THE QUALITY OF TEACHERS - Kappey Laiv; Mardhatillah Mardhatillah (Sensei International Journal of Education and Linguistic, 2022)
This study tries to describe the managerial competence of school principals, to describe the quality of teachers, then to analyze the managerial competencies of principals to improve teacher quality both partially and simultaneously in Karawang, Wadas. Qualitative methods, namely through observation, interviews and documentation. The results of this study indicate that the principal's managerial competence to improve the overall quality of teachers is going well, the principal makes every effort to carry out his duties as a leader or manager. Syllabus and curriculum programs that have gone well as planned since the founding of the school. Then the concept of the principal leads to the vision mission of the school, and applies open managerial concepts in management. The principal always works together, coordinates with all related elements and always provides motivation to teachers and students. Constantly monitoring, evaluating and evaluating and controlling school equipment.